PRODUKSI BIOMASSA DAN KARBON BAMBU PETUNG (Dendrocalamus asper) DI HUTAN RAKYAT AKIBAT ERUPSI MERAPI TAHUN 2010 - , ERWIN DAMAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Community forest has a considerable role in controlling global warming through its function as a carbon sequestration. Bamboo is a typical plant dominating the Community Forests in Ngandong Sub-village Girikerto Village Turi Sub-district Sleman District of Yogyakarta Special Province. A large number of bamboo did not survive as the eruption of Merapi causing the loss of biomass and carbon of the community forest ecosystems in the area. It can be seen from the remained of bamboo stumps which are interesting to be observed, how the influence of the eruption on the production of biomass and carbon is. This study aims to determine the biomass and carbon production of bamboo petung (Dedrocalamus asper) and to figure out the biomass and carbon production of bamboo petung (Dedrocalamus asper) after the eruption of Merapi in 2010. The research was conducted in the Community Forests in Ngandong Sub-village Girikerto Village Turi Sub-district Sleman District. The methods used to collect the field data is purposive sampling for determining the respondent who are the owner of bamboo petung (Dedrocalamus asper) forest. Meanwhile, field measurements were conducted by the inventory of performing bamboo petung census, both on bamboo diameter, stumps, interviews, and distributing questionnaires to find out the effect of the Merapi eruption. This study provides information on the total amount of biomass of bamboo petung in Ngandong Sub-village Girikerto Village Turi Sub-district Sleman District Yogyakarta Special Province, is 226,1 ton/ha. Whereas the total carbon in the Community Forest of Ngandong is 108,84 ton/ha, total carbon absorbed in the Community Forest of Ngandongs is 399,448 ton/ha and total production of bamboo is 149,180 ton/ha in a year. Merapi eruption in 2010 had significant effect on bamboo biomass production in Ngandong Community Forests, as the result of paired samples t-test.